Unlocking IP-backed financing series : country perspectives. (World Intellectual Property Organization, 2024)
"This report gives an account of Türkiye's Journey in the 'Unlocking IP-backed Financing Series' - looking at the challenges as well as government-backed initiatives and commitments to facilitate activities supporting small and medium-sized enterprises (SMEs)."